Improving German Listening Competence by the NURS Teaching Model - Nurming Saleh; Muh. Anwar; Misnawaty Usman (Makassar State University, 2021)
Abstract. Listening is a receptive language competence named as the beginning of the catching on information, and it will be helpfully on the ideas developing. This study is a classroom action research (CAR) and aimed at German listening competence increase of students by implementing the NURS teaching model. NURS is an abbreviation of Nature, Unique, Relevant, and Situational. It is a didactic, constructively, metacognitive, humanly, intercultural, instructional, and technological-based learning procedure. Kemmis and Taggar model consisting of planning, action, observation, and reflection for every cycle, was utilized to implement this CAR in the German educational department at the Faculty of Language and Literature 25 students in the second semester as the research sample with two circles. The syllabus, teaching plan, student activity sheet, and listening formative test were implemented as the research instrument. The data analyzed by using percentage techniques. The result shows that the average student's German listening competence in the first cycle is 46. After they learned in the second, they could not be in minimum score standard 75 because their average score is 61. Their competence percentage increased by 35.16% to 81.16. Another important thing about using the NURS teaching model on learning German is the positive effect on the teacher's teaching skills, like management of teaching, time, and how to make students more enthusiastic during the learning process. It can be concluded that the NURS teaching model can improve the student's German listening competence in the German educational department at the Faculty of Language and Literature of Makassar State University. Keywords: Classroom Action Research, NURS Teaching Model, German, Listening Competence